2010
DOI: 10.3233/jad-2010-1399
|View full text |Cite
|
Sign up to set email alerts
|

Isolated and Joint Effects of Tobacco and Alcohol Consumption on Risk of Alzheimer's Disease

Abstract: Abstract. The roles of smoking and alcohol on the development of Alzheimer's disease (AD) remain unclear. We performed a case-control study on the effects of both exposures before the age of onset of the disease in the cases (and same reference age for their age-matched controls) on disease risk. Interviews were conducted with population controls (n = 246) and relatives of cases (n = 176) identified through local Alzheimer's Disease Associations. Logistic regression models were built adjusting by gender, age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 29 publications
(47 reference statements)
1
25
0
Order By: Relevance
“…Finally, smoking may be a significant confounder of alcohol effects; and thus, both may not only individually affect dementia and cognitive decline but each may also modify the effects of the other. In fact, there were several studies focused on alcohol and cognitive impairment or decline, in which there was no evidence of an interaction between alcohol and smoking on cognitive measures, with a few notable exceptions (Panza et al ., ; Garcia et al ., ). The overall findings from three Canadian data sets suggested that smoking may reduce the risk of dementia among drinkers (Tyas et al ., ), whereas another recent study reported that these interactions were significant only for wine and smoking, suggesting that ingredients other than ethanol in wine may be protective against the adverse effects of smoking or, of course, it could suggest that there is higher consumption of wine among smokers compared with non‐smokers (Mehlig et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, smoking may be a significant confounder of alcohol effects; and thus, both may not only individually affect dementia and cognitive decline but each may also modify the effects of the other. In fact, there were several studies focused on alcohol and cognitive impairment or decline, in which there was no evidence of an interaction between alcohol and smoking on cognitive measures, with a few notable exceptions (Panza et al ., ; Garcia et al ., ). The overall findings from three Canadian data sets suggested that smoking may reduce the risk of dementia among drinkers (Tyas et al ., ), whereas another recent study reported that these interactions were significant only for wine and smoking, suggesting that ingredients other than ethanol in wine may be protective against the adverse effects of smoking or, of course, it could suggest that there is higher consumption of wine among smokers compared with non‐smokers (Mehlig et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that using separate questions to assess the consumption of beer, wine, and liquor reduces the risk of underreporting the amount of alcohol consumed by the patients 33 and is a commonly used approach in studies that include self-reported measures of alcohol consumption. 34,35 …”
Section: Methodsmentioning
confidence: 99%
“…When accounting for APOE ε4 carrier status several studies have found that ε4 carriers have a greater risk of AD associated with tobacco use than non-carriers (20, 26), although some have found no association (27). In one study, smokers who were ε4 carriers had lower auditory-verbal learning and memory scores compared to smokers who were non-carriers and compared to non-smokers regardless of ε4 carrier status (26).…”
Section: Multi-modal Lifestyle Considerationsmentioning
confidence: 99%
“…Similarly, in other studies ε4 carriers who consumed alcohol one or more times per month had a higher risk of AD than those who never consumed alcohol (20) and the risk of AD for ε4 carriers increased with increasing amounts of alcohol consumption (32). While another study showed that alcohol consumption was associated with a decreased risk of AD for ε4 carrier women, this study was conducted retrospectively through interviews with relatives and only had ε4 carrier status for 64% of cases and for none of the controls (27). Overall, the majority of evidence suggests that alcohol consumption for AD prevention may need to be tailored to ε4 carrier status.…”
Section: Multi-modal Lifestyle Considerationsmentioning
confidence: 99%